THIN CAPITALIZATION, SALES GROWTH, CAPITAL INTENSITY ON TAX AVOIDANCE: INSTITUTIONAL OWNERSHIP PERSPECTIVE AS MODERATION - Anarkie, Putri; Ernandi, Herman; Furi, Diana Retno; Efendi, Feny Sabella (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Objective: This study aims to examine the effect of thin capitalization, sales growth, and capital intensity on tax avoidance with institutional ownership as a moderating variable. Method: This type of research is quantitative research. The population in this study were food and beverage sub-sector manufacturing companies listed on the IDX in 2023 - 2025. The sample obtained were 105 companies using purposive sampling techniques. The data analysis technique in this study uses software (SPSS) Statistics version 26. Results: The results show that thin capitalization and sales growth have an effect on tax avoidance, while capital intensity has no effect on tax avoidance. Novelty: Institutional ownership is able to moderate the influence of thin capitalization and sales growth on tax avoidance, while institutional ownership is unable to moderate the influence of capital intensity on tax avoidance.